How microfinance empowers women in Côte d’Ivoire - Binaté Fofana, Namizata; Antonides, Gerrit; Niehof, Anke; van Ophem, Johan A. C. (Review of Economics of the Household, 2015)
This study deals with the effect of microcredit on women’s livelihood and empowerment in rural areas of Cote d’Ivoire. A cross-section survey was conducted among 185 borrowers from two microfinance institutions and 209 nonborrowers in rural areas of Cote d’Ivoire. In addition, a focus group discussion was held with each of the two women groups. After matching the two groups on the probability of obtaining credit, we found that the microcredit group on average had a higher income and a higher value of household assets than the non-borrowers. No differences in the value of personal women’s assets were found. Furthermore, on one hand women’s decision-making power in the household, as indicated by their strategic gender needs, was positively related to the probability of obtaining microcredit. On the other hand receiving microcredit tended to increase their decisionmaking power.
Keywords: OFDIG; afrique; autodétermination; côte d'ivoire; discipline; femmes*; microfinance; militance; ressource en ligne; régions géographiques; sciences de la gestion; thématiques; économie

"Prolétaires de tous les pays, qui lave vos chaussettes?" Dialogue entre Delphy, Marx et les marxistes - Blais, Mélissa; Courcy, Isabelle (Nouveaux cahiers du socialisme, 2010)
Keywords: approches et analyses; capitalisme; discipline; fem1000; féminisme matérialiste; militance; patriarcat; premier cycle; rapports sociaux de sexe; ressource en ligne; science politique et droit; sciences de la gestion; sciences humaines; sociologie; systèmes d'oppression; thématiques; économie